Pulsating heat pipe and embedded heat pipe heat spreaders for modular electronics cooling - Sai Kiran Hota; Kuan-Lin Lee; Brett Leitherer; George Elias; Greg Hoeschele; Srujan Rokkam (Case Studies in Thermal Engineering, 2023)
Two-phase-based heat spreaders are highly sought electronics cooling solutions due to their superior thermal performance over conventional conduction plates. Along with good thermal performance, Pulsating Heat Pipes (PHPs) potentially have thickness, shape matching and cost benefits over Embedded Heat Pipe (EHP) heat spreader solutions. In this manuscript, the thermal performance of PHP charged with three different fluids-propylene, R245fa, and acetone was experimentally determined for different sink temperatures and compared to an EHP heat spreader. A mathematical model to predict the thermal performance of the PHP was developed and validated against experimental results. It was determined that at low sink temperatures, PHP charged with propylene performs better than or similar to an EHP heat spreader with up to 7.8 times higher effective thermal conductivity over a conduction plate. However, at moderate temperatures above >40 °C, propylene PHP dries out faster than the EHP plate. PHP performance with R245fa and acetone improves with increasing heater power. Effective thermal conductivity improved by 2.5 times with R245fa PHP and by 4 times with acetone PHP over the conventional plate but was lower than the EHP plate whose effective thermal conductivity was 17.3 times higher. However, weight comparison showed PHP to be lighter than the EHPs.